UJI AKTIVITAS ASAP CAIR CANGKANG BUAH KARET (Hevea brassiliensis) DAN APLIKASINYA DALAM PENGHAMBATAN KETENGIKAN DAGING SAPI - Haulia Dwi Putri; Sumpono Sumpono; Nurhamidah Nurhamidah (ALOTROP, 2018)
This research was aimed to know the degree of Fenol compound, total acid and the activity of liquid smoke of Rubber (Hevea brassiliensis) Seed Shell also the application in obstructing the rancidity of beef. The Fenol compound was determined by using Reagen Follon-Ciocalteu. The total acid was determined by using the method of titrated acids.The ability as the antioxidant was tested by DPPH method and the ability of obstructing the rancidity of beef was done by measuring the alteration of TBA value in beef as long as saved. The result was shown the fenol compound in liquid smoke of Rubber Seed Shell as much as 0,84 % and the acetic acid content was 4.725%. The antioxidant test was produced IC50 value as much as 101.27 ppm. According to the IC50 value which got from the test that the liquid smoke of Rubber Seed Shell were included in moderate category. The increment of the liquid smoke of Rubber Seed Shell were able to suppress the rancidity of beef during the storage time. It was marked by the decreasing of TBA value in beef as given in treatment A1 (liquid smoke 4% ) and A2 liquid smoke 6%. The treatment without the liquid smoke (A0) increased the TBA value from 0.05 mgMDA/Kg on day (0) to 0.615 mgMDA/Kg on day 6. The treatment of concentration liquid smoke 4% (A1)  increased  from  0.039  mgMDA/Kg  on  day  (0) to  0.395  mgMDA/Kg  on  day  6.  The  treatment  of concentration liquid smoke 6% (A2) increased from 0.031 mgMDA/Kg on day 0 to 0.209 mgMDA/Kg on day 6.